The feast of Toxcatl in the Florentine Codex: ekphrasis as etiology and preservation. Issue 4 (2nd October 2021) - Nelson, Jennifer
Abstract: Ekphrasis, understood as a metaphor for encounter, serves as a literal vessel for an encounter between Nahua and Spanish worldviews in the illustrated bilingual Spanish and Nahuatl encyclopedia Historia general de las cosas de Nueva España (mostly written 1547–78), overseen by Bernardino de Sahagún in collaboration with Nahua scholars. Crucially, the function of ekphrasis—intensified verbal description of visual artifice—differed between Spanish and Nahua users of the encyclopedia, both in general and in this context. The twin missions of the text, to diagnose Nahua deviance from Christianity, and to record the Nahua world and its practices, directly conflict. This essay examines the differences between the side-by-side Spanish and Nahuatl accounts of a major Mexica ceremony, Toxcatl, with a special focus on rhetorical discrepancies between the two. It also argues that the unusually explicitly gruesome illustrations of this section may have functioned differently for the two audiences: as iconographic aids to identification of idolatrous ritual for the Spanish, but for a Nahua audience as ongoing ekphrasis-prompts, extending the ritual.